Distribution Catch Size and Condition Factor of Giant River Prawn (Macrobrachium rosenbergii) in the Kayu Arang River, West Bangka Regency, Bangka Belitung Islands - Priyambada, Agung; Ferdiansyah, Ferdiansyah; Kelvin, Kelvin (Jurnal Biologi Tropis, 2025)
The Kayu Arang River represents a natural habitat with potential for the sustainable exploitation of the giant freshwater prawn (Macrobrachium rosenbergii). High consumer demand has led to increased harvesting pressure in the wild. The captured prawns exhibit a wide size range, from small to large individuals. Therefore, it is essential to consider size eligibility in harvesting to ensure long-term resource sustainability. This study aimed to analyze the size distribution, catch eligibility, length–weight relationship, and condition factor of M. rosenbergii in the Kayu Arang River. Field sampling was conducted in September 2023 using handline fishing gear at 20 designated stations. Results showed that male prawns ranged from 11.10 to 25.70 cm in total length, with dominant catch sizes between 13.90–15.70 cm and 15.80–17.60 cm. Female prawns ranged from 10.10 to 17.70 cm, with a dominant size class of 12.00–13.80 cm. Legally catchable males were found at stations 1, 2, 6, 9, 10, and 12; females at stations 7, 8, 9, and 12. The length–weight relationship for males followed the equation W = 0.0081L³.1682 (N = 100; R² = 0.9116), indicating positive allometric growth, while females followed W = 0.0142L².9401 (N = 110; R² = 0.6533), indicating negative allometric growth. The condition factor ranged from 0.59 to 1.75 for males (mean: 1.02) and 0.53 to 1.89 for females (mean: 1.04), suggesting that most individuals were in healthy condition.